2019
DOI: 10.1039/c9nr06512a
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-targeting of ultra-small nanoparticles enhances imaging sensitivity and enables longitudinal tracking of multiple myeloma

Abstract: Monitoring malignant progression and disease recurrence post-therapy are central challenges to improving the outcomes of patients with multiple myeloma (MM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
3
26
1
Order By: Relevance
“…hence improving tumor cells accumulation. [71] However, because of their size, a high drug loading is difficult to achieve, orienting their use mostly for medical imaging applications. [33,34,71] At the opposite, the biodistribution and pharmacokinetics properties of large NPs (> 50 nm diameter) are dictated by the NP, resulting in a large accumulation in the liver and lymph nodes.…”
Section: Nanomedicine To Improve Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…hence improving tumor cells accumulation. [71] However, because of their size, a high drug loading is difficult to achieve, orienting their use mostly for medical imaging applications. [33,34,71] At the opposite, the biodistribution and pharmacokinetics properties of large NPs (> 50 nm diameter) are dictated by the NP, resulting in a large accumulation in the liver and lymph nodes.…”
Section: Nanomedicine To Improve Immunotherapymentioning
confidence: 99%
“…[71] However, because of their size, a high drug loading is difficult to achieve, orienting their use mostly for medical imaging applications. [33,34,71] At the opposite, the biodistribution and pharmacokinetics properties of large NPs (> 50 nm diameter) are dictated by the NP, resulting in a large accumulation in the liver and lymph nodes. [72,73] This preferential accumulation into lymphatic vessels and lymph nodes is of interest to target immune cells for vaccination approach or for neoantigen recruitment after radiotherapy.…”
Section: Nanomedicine To Improve Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Recently, immunoPET radiotracers have been translated into the clinic due to the specificity of selected antibodies and the high sensitivity of PET imaging [9,10] . Preclinical studies involving immunoPET radiotracers (using antibodies or nanobodies) [11][12][13] and antibodyconjugated MRI tracers [14] have demonstrated the possibility of significantly improving longitudinal monitoring of MM. The development of novel immunoPET radiotracers is of keen interest due to their better signal-to-noise ratios (SNRs) over MRIbased methods and their ability to detect small clusters of cells, potentially enabling the identification of minimal residual disease (MRD), which is currently difficult with passive contrast agents for PET imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging these promising results, we designed an innovative approach that targets the B-cell maturation antigen (BCMA) that is widely used as a therapeutic target in MM and that is highly expressed at all stages of the disease; notably, this approach differs from traditional methods that have instead targeted CD38, which is a transmembrane glycoprotein that is almost exclusively expressed on MM cells. [14] BCMA is a known target for chimeric antigen receptor (CAR) T-cell [15] and bispecific antibody therapy; [16] but, it has yet to be adopted for MM imaging. [17] While we previously successfully demonstrated that targeting BCMA for preclinical MRI-based imaging of MM is a relevant approach, [14] here, we hypothesized that the use of a immuno-nanoPET radiotracer would enable a decrease in the amount of mAb needed for injection in comparison to the amounts of im-munoPET radiotracer required to improve the sensitivity of PET imaging.…”
Section: Introductionmentioning
confidence: 99%